2010
DOI: 10.1136/bjo.2010.191585
|View full text |Cite
|
Sign up to set email alerts
|

Ocular complications in patients with lung transplants

Abstract: Many ocular conditions can occur in patients with lung transplants. Ocular infectious complications were uncommon but may be associated with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Tarabishy et al reported the finding in 13 (28.3%) out of 46 lung transplant recipients, making it the most common ophthalmologic complication in this population (59). Data from other SOT recipients show a similar trend.…”
Section: Posterior Subcapsular Cataract (Psc)mentioning
confidence: 57%
“…Tarabishy et al reported the finding in 13 (28.3%) out of 46 lung transplant recipients, making it the most common ophthalmologic complication in this population (59). Data from other SOT recipients show a similar trend.…”
Section: Posterior Subcapsular Cataract (Psc)mentioning
confidence: 57%
“…We found reports on 121 cases of mucormycosis in LTR. Data regarding infection site and outcome were available for 53 patients (Figure ), whereas detailed clinical and therapeutic data were available for 34 patients, for which the data regarding our series were also added, to total 40 patients (Table ) . Thirty‐four of the 121 published cases referred to airway colonization with Mucorales without clinical, radiological, or histological evidence of invasive disease; however, some cases affected management, leading to reduced immunosuppression or to initiation of antifungal therapy .…”
Section: Resultsmentioning
confidence: 99%
“…Tarabishy et al found that the most common ocular abnormality following lung transplant was posterior subcapsular cataract, followed by infectious ocular complications 34 . High levels of immunosuppression, advanced age, drug-specific side effects, underlying comorbidities such as diabetes mellitus, have been suggested to play a role in pathogensis 35 .…”
Section: Discussionmentioning
confidence: 99%